(untitled) (Nóema, 2017)
This paper concerns the relation between philosophy and philosophical practice in the husserlian paradigm of phenomenology. The role and the method that Husserl conceives for the philosopher are related unavoidably to his theoretical system. During his long and hard work, he deals with the question of the genesis of logic in the platonic-aristotelic dichotomy, with the connection between philosophy and objective sciences and with the problem of phenomenology as descriptive practice. Thanks to this reflections, in The crisis of european sciences he conceives the role of the philosopher with a precise historical and ethical function. This new model represents one of the last philosophical systems as a universal theory.